Synthesis of Flower-Like CuBi2O4 Microspheres and Its Photocatalytic Activity - Muankaew, Rapeepat; Banphot, Chompunut; Thammaacheep, Punyanuch; Jannoey, Panatda; Khanitchaidecha, Wilawan; Nakaruk, Auppatham; Channei, Duangdao (Trends in Sciences, 2024)
In this study, visible-light copper bismuth oxide (CuBi2O4) photocatalyst were synthesized via co-precipitation (CuBi2O4-C) and microwave-assisted methods (CuBi2O4-M). The X-ray powder diffraction (XRD) analysis reveals the presence of pure tetragonal, along with band gaps of 2.9 eV in both samples. The microwave-assisted method produced flower-like CuBi2O4 microspheres, which had a larger BET surface area and demonstrated the highest photocatalytic performance, approximately 83.4 % in the decolorization of malachite green (MG) dye under visible light. Therefore, the research suggested a facile strategy for the fast synthesis of CuBi2O4 microspheres under mild reaction conditions. The use of microwave heat treatment is a faster and more efficient way to photocatalyst materials, while also being cost-effective and energy-saving. HIGHLIGHTS The flower-like CuBi2O4 microspheres synthesized via the microwave-assisted method offer a promising approach for efficient and cost-effective photocatalysis, particularly in the degradation of malachite green dye under visible light. This study highlights the potential of microwave synthesis in enhancing the photocatalytic performance of CuBi2O4 materials GRAPHICAL ABSTRACT